2001
DOI: 10.4319/lo.2001.46.3.0514
|View full text |Cite
|
Sign up to set email alerts
|

Bivalve diets in a midwestern U.S. stream: A stable isotope enrichment study

Abstract: This study examined a community of stream bivalves (unionids and fingernail clams) in a second-order woodland stream in southern Michigan using both the natural abundance of 15 N and a 6-week whole-stream 15 N enrichment experiment, as part of the Lotic Intersite Nitrogen eXperiment (LINX). Objectives included addressing what made up the diet of these bivalves and whether suspended algae consumed by bivalves were derived from pelagic phytoplankton imported from an upstream lake or attached algae sloughed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 40 publications
7
141
1
Order By: Relevance
“…In consequence, the organism tends to be isotopically enriched in 13 C or 15 N (to respect the equilibrium). But classical enrichment factors have been calculated mainly for terrestrial organisms (De Niro &Epstein, 1978, 81) and a large range is found in the literature (Mingawa and Wada, 1984;Raikow and Hamilton, 2001). We therefore believe that there is a need to validate for each species the isotopic fractionation between diet and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In consequence, the organism tends to be isotopically enriched in 13 C or 15 N (to respect the equilibrium). But classical enrichment factors have been calculated mainly for terrestrial organisms (De Niro &Epstein, 1978, 81) and a large range is found in the literature (Mingawa and Wada, 1984;Raikow and Hamilton, 2001). We therefore believe that there is a need to validate for each species the isotopic fractionation between diet and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…First, as already mentioned, a selective assimilation of one component of the SPOM with high isotopic value could occur. Indeed, Raikow and Hamilton (2001) postulated that differential, rather than uniform, assimilation of food resource components within the SPOM could occur. A selective assimilation of nutrients from diet could also be an explanation and further work on stable isotopic composition of the different biochemical fractions of the SPOM would be of interest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations